The Allure of Korean dramas and Its Impact on the Changes of Students' Religious Practices in Islamic State University of Raden Intan Lampung, Indonesia - Yani, Juli Fitri; Hasanah, Uswatun (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
The rapidly increasing popularity of K-dramas among Muslim students in Indonesia has raised concerns about their impact on their religious values, as intense exposure to the culture and lifestyle depicted in K-dramas may influence Muslim students' religious perceptions and practices. In this case, this study aims to examine whether there is a correlation between the intensity of watching K-dramas and changes in religious values and practice among Islamic Education students from the batch of 2019 at UIN Raden Intan Lampung. The research uses a quantitative survey method by collecting data through a Likert scale questionnaire. The data analysis used Pearson Product-moment correlation analysis and simple linear regression. The results indicate that a significance value of 0.011 < 0.05 was obtained, leading to the rejection of H0 and acceptance of H1. This suggests a significant influence between the intensity of watching K-dramas and changes in student religious values and practice. Therefore, it is recommended that students be wiser in using their time and increase their religious activities. Moreover, educational institutions should also strengthen programs that support religious practices.